Effect of a single rectal fecal microbiota transplantation on clinical severity and fecal microbial communities in dogs with chronic inflammatory enteropathy - Jorge Pérez‐Accino; Mazdak Salavati; Laura Glendinning; Silke Salavati Schmitz (Journal of Veterinary Internal Medicine)
Abstract Background Fecal microbiota transplantation (FMT) has been advocated as a treatment for chronic enteropathy (CE) in dogs. However, so far only short‐term clinical effects have been reported whereas the effect on the microbiota remains unexplored. Hypothesis/Objectives Assess if a single FMT enema can lead to clinical improvement in dogs with CE when accompanied by presumed favorable microbiota changes. The effect of glycerol as a cryopreservative when storing FMT preparations also was assessed. Animals Seven dogs with CE that received FMTs from 2 healthy donor dogs. Materials and Methods Six dogs received a single FMT, 1 dog received 3 consecutive FMTs. Canine chronic enteropathy clinical activity index (CCECAI) and fecal samples were obtained before (Day 0), and 7, 30 and 90 days after FMT. Samples were stored with and without 10% glycerol. Sequencing of microbiota (16S rRNA, Illumina) was performed and compared by accepted analysis pipelines. Results Median CCECAI before FMT was 8 (range, 5‐14), decreased to a median of 3 (range, 1‐12) within 1 week and a median of 1 (range, 0‐12) by Day 30 (P < .01), with an average duration of response of approximately 10 weeks. Significant variation in the donors' microbiota composition was observed across different donations. Recipient microbiota composition or diversity did not change over time. Glycerol addition was associated with a difference in microbiota composition (P ≤ .001). Conclusions and Clinical Importance A single FMT can be considered an appropriate treatment in dogs with CE, but consistent microbiota changes were not observed.